1970
DOI: 10.4141/cjps70-008
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Initial Seed Weight and Mature Plant Characters in Spring Wheat

Abstract: For tach g{ the_ three spring rvheat cultivars, mulae were calculated for all traits. The size rembrna'.lhaicher. and Manitou, the weight of the individual seeds planted was shown to ol.approximately 900 seeds from 30 randomly account for 2.5 to 4.5To'of the observed variaselected heads was recorded. These seeds were tions in yield and other mature plant characgrown to rnaturity in.the field and mature ters, including the number of heids produced plant characlers associaled with yield were per plant. llead num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

1981
1981
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 4 publications
0
21
0
1
Order By: Relevance
“…This result showed that the yield varied with the cultivar more greatly than with the storage period. Tamura et al (1957), Waldron (1941), Pinthus and Osher (1966) and Austenson and Walton (1970) reported that the larger the seeds, the more vigorous the growth and the greater the grain yield in wheat. Kaufmann and Mcfadden (1963) and Demirlicakmak et al (1963) reported the same result in barley.…”
Section: Methodsmentioning
confidence: 99%
“…This result showed that the yield varied with the cultivar more greatly than with the storage period. Tamura et al (1957), Waldron (1941), Pinthus and Osher (1966) and Austenson and Walton (1970) reported that the larger the seeds, the more vigorous the growth and the greater the grain yield in wheat. Kaufmann and Mcfadden (1963) and Demirlicakmak et al (1963) reported the same result in barley.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, Sp2 increased grain weight and total yield of wheat under field condition. Previous study indicated that total yield of wheat was significantly correlated (P < 0.01) with initial seed weights (Austen-Son and Walton 1970). Pervious experiments also showed that inoculation of wheat with Azospirillum increases the productivity of wheat (Santa et al 2004;Piccinin et al 2011Piccinin et al , 2013Ayyaz et al 2016).…”
Section: Discussionmentioning
confidence: 92%
“…Em outras espécies botâ-nicas, estudos semelhantes mostraram que sementes maiores apresentaram índices_ superiores (AUSTENSON & WALTON, 1970;RIES & EVERSON, 1973;FRAZÃO et al, 1983). Entretanto, o valor de germinação final do craveiro-da-índia (35 dias) foi bastante afetado pelo tamanho da semente; as grandes e médias mostraram germinação superior às do lote original e, as pequenas, os menores valores.…”
Section: Resultsunclassified